Power Series Transform in Cryptology and ASCII - Gencoglu, Muharrem Tuncay; Baleanu, Dumitru (Springer International Publishing Ag, 2019)
[Abstract Not Available]
International Symposium on Mathematical Methods in Engineering (MME) -- APR 27-29, 2017 -- Cankaya Univ, Ankara, TURKEY